2018
DOI: 10.1111/cdev.13074
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Relations Between Parental Problem Drinking and Children's Sleep: The Role of Socioeconomic Adversity

Abstract: Reciprocal relations between parental problem drinking (PPD) and children's sleep were examined longitudinally, and socioeconomic status was considered as a moderating variable. At Wave 1, 280 children (M = 10.33) and their parent(s) participated, and 275 families returned 1 year later. At both waves, parent(s) reported on PD and children wore actigraphs that measured established sleep parameters. After controlling for autoregressive effects, fathers' PD predicted reduced sleep duration and efficiency in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 64 publications
1
9
2
Order By: Relevance
“…For example, it is possible that early SES may directly influence children’s sleep quality which, in turn, may influence the quality of the home environment including parent responsivity, parental autonomy granting, or conflict in the home. Although no one has considered bidirectional influences of the home environment and sleep, some recent work has considered bidirectional associations between characteristics of the parent and children’s sleep, showing that parental drinking was prospectively associated with shorter sleep duration and lower sleep efficiency in children, but that greater child awakenings were also prospectively associated with greater paternal problem drinking (Kelly and El-Sheikh, 2018). Future work should aim to include both concurrent and prospective prediction of sleep to understand potential bidirectional longitudinal associations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is possible that early SES may directly influence children’s sleep quality which, in turn, may influence the quality of the home environment including parent responsivity, parental autonomy granting, or conflict in the home. Although no one has considered bidirectional influences of the home environment and sleep, some recent work has considered bidirectional associations between characteristics of the parent and children’s sleep, showing that parental drinking was prospectively associated with shorter sleep duration and lower sleep efficiency in children, but that greater child awakenings were also prospectively associated with greater paternal problem drinking (Kelly and El-Sheikh, 2018). Future work should aim to include both concurrent and prospective prediction of sleep to understand potential bidirectional longitudinal associations.…”
Section: Discussionmentioning
confidence: 99%
“…A later study by Kelly and El-Sheikh (2019) longitudinally investigated the relationship between parental drinking problems and adolescents' sleep. It showed adolescents' sleep duration and efficiency decreasing gradually, over a period of time, if the father had a drinking problem, along with regular occurrences of adolescents requiring greater amount of time to wake up [29]. Another study reported that school-age children with alcoholic parents had shorter sleep durations and greater nighttime activities than children of parents with low alcohol consumption [42].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the data from the Korean Children and Youth Panel Survey, parents' occupation was identified as a factor predicting the poverty of children's sleep duration and sleep time [25]. In addition, gender [26,27], parental drinking [28][29][30], and parental sleep duration [21,31] were found to have an effect on adolescents and children's sleep duration, these were selected as a variable that can be used in the KNHANES data. sleep duration (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Household chaos yet has been equally linked to socio-economic risk, negative life events, less favorable parenting and less emotional availability at bedtime [58] . Thus bi- or multidirectionality can be put forward in studies, as they each show, on the one hand, the risk factors such as parental drinking [59] , child's sleep problems [60] and, on the other hand, the protective factors such as emotional security in family interactions [61] , time spent to sleep while in bed [62] , physical activity [63] . Similarly, moderator and mediator effects have been a topic of great interest [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%